1999
DOI: 10.1159/000053163
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Leptin in Sexual Maturation and Puberty?

Abstract: Leptin, the ob gene product, is involved in the regulation of body weight in rodents, primates and humans. It provides a molecular basis for the lipostatic theory of the regulation of energy balance. White adipose tissue and placenta are the main sites of leptin synthesis. There is also evidence of ob gene expression in brown fat. Leptin seems to play a key role in the control of body fat stores by coordinated regulation of feeding behaviour, metabolic rate, autonomic nervous system regulation and body energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 44 publications
2
30
0
6
Order By: Relevance
“…Leptin may be the main mediator of the influence of sex hormones on adipocytes: testosterone has been found to suppress leptin synthesis by adipocytes both in vivo and in vitro (24). In healthy normal men, suppression of endogenous testosterone production with gonadotrophin-releasing hormone (GnRH) agonists (25) or GnRH antagonists (26) results in an increase of leptin serum levels and, vice versa, testosterone administration to normal healthy men results in reduced leptin serum levels (25).…”
Section: Discussionmentioning
confidence: 99%
“…Leptin may be the main mediator of the influence of sex hormones on adipocytes: testosterone has been found to suppress leptin synthesis by adipocytes both in vivo and in vitro (24). In healthy normal men, suppression of endogenous testosterone production with gonadotrophin-releasing hormone (GnRH) agonists (25) or GnRH antagonists (26) results in an increase of leptin serum levels and, vice versa, testosterone administration to normal healthy men results in reduced leptin serum levels (25).…”
Section: Discussionmentioning
confidence: 99%
“…Leptin, the product of the OB gene located at 7q31.3, provides a molecular basis for the lipostatic theory of the regulation of energy balance (4). It has become clear that leptin also plays an important role in reproduction, both during pregnancy and early neonatal life (4).…”
Section: Leptin and Adiponectinmentioning
confidence: 99%
“…Biological effects of leptin include the suppression of food intake and the increase of energy expenditure, and consequently, the regulation of body weight (2)(3)(4)(5). Several studies have suggested that leptin also influences sexual progression through puberty (6)(7)(8). Impaired growth and pubertal delay have been observed in children with diabetes (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%